An unusual case of complete atrioventricular block causing Takotsubo syndrome - Abhishek Rathore; Bharatraj Banavalikar; Jayaprakash Shenthar; Debashish Acharya; Javed Parvez; Kikkeri Hemanna Setty Srinivasa (Indian Pacing and Electrophysiology Journal, 2018)
Complete atrioventricular (AV) block in association with Takotsubo syndrome (TS) has been well recognized, but the cause and effect relationship has not been elucidated. We describe a 78-year-old female who presented with complete AV block but one week later developed new-onset, diffuse T-wave inversions, QT prolongation, and acceleration of junctional escape rate. Left ventriculogram revealed features typical of TS. One year after permanent pacemaker implantation, complete AV block persisted despite the reversal of wall motion defects implying that conduction abnormality was the trigger of TS rather than its consequence.